Effects of an intensive lifestyle intervention program on portal hypertension in patients with cirrhosis and obesity: The SportDiet study. Issue 4 (6th March 2017) - Berzigotti, Annalisa; Albillos, Agustín; Villanueva, Candid; Genescá, Joan; Ardevol, Alba; Augustín, Salvador; Calleja, Jose Luis; Bañares, Rafael; García‐Pagán, Juan Carlos; Mesonero, Francisco; Bosch, Jaime; ,
Abstract : Obesity increases the risk of clinical decompensation in cirrhosis, possibly by increasing portal pressure. Whether weight reduction can be safely achieved through lifestyle (LS) changes (diet and exercise) in overweight/obese patients with cirrhosis, and if weight loss reduces portal pressure in this setting, is unknown. This prospective, multicentric, uncontrolled pilot study enrolled patients with compensated cirrhosis, portal hypertension (hepatic venous pressure gradient [HVPG] ≥6 mm Hg), and body mass index (BMI) ≥26 kg/m 2 in an intensive 16‐week LS intervention program (personalized hypocaloric normoproteic diet and 60 min/wk of supervised physical activity). We measured HVPG, body weight (BW) and composition, adipokines, health‐related quality of life, and safety data before and after the intervention. Changes in HVPG and BW were predefined as clinically relevant if ≥10% and ≥5%, respectively. Safety and BW were reassessed after 6 months. 60 patients were included and 50 completed the study (56 ± 8 years old; 62% male; nonalcoholic steatohepatitis etiology 24%; BMI 33.3 ± 3.2 kg/m 2 ; Child A 92%; HVPG ≥10 mm Hg, 72%). LS intervention significantly decreased BW (average, –5.0 ± 4.0 kg; P < 0.0001), by ≥5% in 52% and ≥10% in 16%. HVPG also significantly decreased (from 13.9 ± 5.6 to 12.3 ± 5.2 mm Hg; P < 0.0001), by ≥10% in 42% and ≥20% in 24%. A ≥10% BW loss was associated with a greater decrease in HVPG (–23.7 ± 19.9% vs. –8.2 ± 16.6%; P = 0.024). No episodes of clinical decompensation occurred. Weight loss achieved at 16 weeks was maintained at 6 months; Child and Model for End‐Stage Liver Disease scores did not change. Conclusion : Sixteen weeks of diet and moderate exercise were safe and reduced BW and portal pressure in overweight/obese patients with cirrhosis and portal hypertension. (Hepatology 2017;65:1293‐1305).